The Sense of The Words in The Political and Legal Articles in December 2018 Edition of Kompas Newspaper: The Semantics Study - Haerudin (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
The porpuse of this research is, (1) to analyze and describe the meaning of the words contained in the political and legal article in the December 2018 of Kompas daily. The method of research used is a method of content analysis with a qualitative approach. Research data on the sense of words found in political and legal articles in a Kompas newspaper. Based on research results, it can be concluded that the study of the work contained 54 dates of grammatical significance of 15 forms, a nonreferential meaning of 12 forms, a denonative meaning of 1 form, a conotative meaning of 6 forms, a contextual meaning of 9 forms, an idiomatic meaning of 10 forms, and a cystic meaning of 2 forms. Thus, from the results of the analysis shows the meaning of the words contained in the 2018 edition of the political and judicial article the Kompas daily is a grammatical meaning, a nonreferential meaning, a denotatof meaning, a conmutative meaning, meaning of the term, idiomatic meaning, and meaning of chias. Abstrak Penelitian ini bertujuan bertujuan untuk (1) menganalisis dan mendeskripsikan makna kata yang terdapat pada rubrik artikel politik dan hukum dalam surat kabar harian Kompas edisi Desember 2018. Metode penelitian yang digunakan adalah metode analisis isi dengan pendekatan kualitatif. Data penelitian berupa makna kata yang terdapat pada rubrik artikel politik dan hukum dalam surat kabar harian kompas. Berdasarkan hasil penelitian, dapat disimpulkan bahwa penelitian yang dilakukan terdapat 54 data yang mengandung makna kata diantaranya ditemukan makna gramatikal 15 bentuk, makna nonreferensial 12 bentuk, makna denonatif 1 bentuk, makna konotatif 6 bentuk, makna istilah 9 bentuk, makna idiomatik 10 bentuk, dan makna kias 2 bentuk. Dengan demikian, dari hasil analisis menunjukkan bahwa makna kata yang terdapat dalam artikel politik dan hukum koran Kompas edisi 2018 adalah makna gramatikal, makna nonrefernsial, makna denotatof, makna konotatif, makna istilah, makna idiomatik, dan makna kias. Kata kunci: makna kata, artikel, semantik